Nicaragua : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2012)
This paper is a report of Nicaragua's performance under the 2007-11 program. The period was marked by a stern financial crisis, price shocks, and disasters, but the program maintained the macroeconomic stability. Although the program had several hurdles, its achievements were remarkable-approval of tax reforms, improvements in banks' framework, power and electricity framework, dwindled poverty rate, and strong foreign relations. Overall, the Board is in high spirits in the triumph of the program in a critical situation though it had some flaws.